A large single ethnicity study of prepulse inhibition in schizophrenia: Separate analysis by sex focusing on effect of symptoms. (November 2016) - Matsuo, Junko; Ota, Miho; Hori, Hiroaki; Hidese, Shinsuke; Teraishi, Toshiya; Ishida, Ikki; Hiraishi, Moeko; Kunugi, Hiroshi
Abstract: Deficits in sensorimotor gating, as measured with prepulse inhibition (PPI), have been considered an endophenotype of schizophrenia. However, the question remains whether these deficits are related to current symptoms. This single site study aimed to explore clinical features related to the modulation of startle reflex in a large sample of Japanese patients with schizophrenia (DSM-IV). The subjects comprised 181 patients and 250 healthy controls matched for age and sex. Schizophrenia symptoms were assessed with the Positive and Negative Syndrome Scale (PANSS). Startle reflex to acoustic stimuli was recorded using a startle stimulus of 115 dB and a prepulse of four different conditions (intensity: 86 dB or 90 dB; lead interval: 60 ms or 120 ms). Patients exhibited significantly reduced startle magnitude ( p  < 0.001), habituation ( p  = 0.001), and PPI (90 dB, 60 ms, p  = 0.016; 90 dB, 120 ms, p  = 0.001) compared with controls. Patients of both sexes exhibited significantly lower habituation and PPI (90 dB, 120 ms) compared with the same sex controls. We could not detect a significant correlation with any clinical variable in the entire patients, however, when men and women were examined separately, there was a negative correlation with the PANSS cognitive domain (ρ = −0.33, p  = 0.008) in men, but not in women. Moreover, when patients were subdivided into four clusters, two clusters with high positive symptoms showed significant PPI deficits in men. Our results suggest that sensorimotor gating is impaired in schizophrenia of both sexes, and PPI deficits may be related to thought disturbance and disorganization in male patients with schizophrenia. Highlights: Patients exhibited significantly reduced startle magnitude, habituation, and PPI. Patients of both sexes exhibited significantly lower habituation and PPI. PPI negatively correlated with the PANSS cognitive domain in men, but not in women.